Tradução comentada de fábulas da obra de Monteiro Lobato para a Libras/ELiS - Melo, Nyce Marcelle de Leon Rocha Vieira de (2023)
This dissertation is an annotated translation of fables from Portuguese to Brazilian sign language, using the ELiS system written. The fables translated (1) O burro na pele de leão, (2) A cabra, o cabrito e o lobo, (3) O peru medroso, (4) A coruja e a águia e (5) A raposa sem rabo. In this undertaking, we describe the reflections and decisions of a macro-structural, micro- structural order and during the writing of facial expressions and mimetic actions in the incorporation of referents. About the commented translation, we base ourselves on Torres (2017) and Zavaglia, Renard and Janczur (2015), on Portella (1983) on the organization of the fables genre and on Pagano (2006) for the definition of description categories. Regarding macrotextual aspects, the text in libras was organized linearly, horizontally, from left to right and in paragraphs, maintaining a parallelism in relation to the text in the source language. The referencing of characters was carried out by incorporating the referent, classifiers, omission and reiteration. There was no use of indexing signs. Regarding the naming of characters in libras, the referent's visual characteristics were preserved, individualizing these charactersand, at the same time, keeping them within a hyperonym of the corresponding animal. The emphasis of the excerpt on morality happened by changing the font color and, during the translation, the literality of the excerpt was preserved, as a way of keeping the proposition's message implicit. On the microtextual aspects, we discuss the use of classifiers and the Surrogate Space as structures that favor a simple, direct and objective language, characteristic of fables, and the adaptation in order to contemplate deaf culture. In order to register the facialexpressions and mimetic actions of the Surrogate Space, we suggest the anticipation and isolated registration of the visographema related to the visographic group movement in ELiS.